Simulation of sample paths and distribution of liu integrals - Behrouz Fathi Vajargah; Sara Ghasemalipour; Maryam Doosti (Journal of Hyperstructures, 2021)
Uncertain process and uncertain integral are important contents of uncertainty theory. In this paper, we study some typesof uncertain integral named Liu integral. Here, we obtained the analytical solution of Liu integral by integration methods. As a new work, we simulated the sample paths and distribution of Liu integral. The simulation method run on some new examples and results are shown.